2017
DOI: 10.2116/analsci.33.47
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Pharmaceutical Cocrystals in Nanosized Pores of Mesoporous Silica

Abstract: The Raman spectroscopy of pharmaceutical cocrystals based on caffeine and oxalic acid in nanosized pores of mesoporous silica has been demonstrated at various molar amounts. The Raman peak shifts of caffeine molecules express the existence of pharmaceutical cocrystals in mesoporous silica. The molar amount dependence of the peak shifts describes that caffeine and oxalic acid cocrystallized on the surface of the nanosized pores and piled up layer by layer. This is the first report that shows the Raman spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…62 Ohita et al also reported cocrystal formation of caffeine-oxalic acid within MPS. 63 Diffusion-Supported Loading (DiSupLo)…”
Section: The Adsorption Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…62 Ohita et al also reported cocrystal formation of caffeine-oxalic acid within MPS. 63 Diffusion-Supported Loading (DiSupLo)…”
Section: The Adsorption Methodsmentioning
confidence: 99%
“…The peak frequencies at 32, 56, and 83 cm –1 are slightly shifted when cocrystals are synthesized in SBA-16, indicating a dominant formation on the surface of SBA-16 without aggregation. 63 …”
Section: Drug-coformer Within Mps Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes optical methods promising for studying fluid adsorption in nanopores, including the smallest ones. In particular, spectroscopic techniques based on Raman scattering allow probing of the analyte confined in nanoporous solids [24][25][26][27][28], thus providing direct information about the phase state and interaction with the pore walls. Fundamentally, the molecule's environment affects its vibrations, including modification of the vibrational transition frequencies.…”
Section: Introductionmentioning
confidence: 99%